Effect of rotational speed on the modal parameters of a helicopter blade based on operational modal analysis approach - Camargo, E. Alexandre; Ambrosio, D. Ricardo; Candido de Sousa, V. [UNESP]; Castillo Zúñiga, D. Fernando [UNESP]; Sartorato, M. [UNESP]; Costa, N.; Luiz Oliveira, [UNESP] (My University, 2024)
An investigation on the effects of rotational speed of a full-scale AS350 helicopter main rotor blade on its modal parameters is presented in this study. An experimental whirl tower apparatus (centrifuge) is employed to apply different levels of centrifugal loads to the blade according to prescribed rotational speeds. The blade is instrumented with strain gauges and accelerometers along its span direction for vibration mode shapes characterization. The vibration data are transmitted by a wireless data acquisition system. The blade is tested at rotational speeds of 15 rpm, 30 rpm and 45 rpm. Operational Modal Analysis and Modal Assurance Criterion methods are applied. The blade natural frequencies increase with increasing rotational speed due to the centrifugal stiffening effect. The first and second blade flap (bending) modes, as well as the first blade torsion mode, are successfully characterized based on the proposed approach.